2013
DOI: 10.1002/pd.4293
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ultrasound evaluation of fetal Hb Bart's disease among pregnancies at risk at 11 to 14 weeks of gestation

Abstract: At 11 to 14 weeks of gestation, sonographic markers can effectively differentiate affected from unaffected pregnancies. The most sensitive marker was CT ratio plus MCA-PSV. Of couples at risk with no any sonographic markers, the risk of having an affected fetus is nearly eliminated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 18 publications
1
54
0
Order By: Relevance
“…We have found that placental enlargement in fetal Hb Bart's disease can occur as early as in the late first trimester, and assessment of placental size is therefore clinically useful. For example, placental thickness assessed by 2D US at 11–14 weeks of gestation can differentiate fetuses with Hb Bart's disease from unaffected fetuses with a sensitivity of 70.0% and a specificity of 63.5% . However, a more reliable measurement technique of placenta size like 3D US and VOCAL, which is theoretically better than placental thickness, should improve the accuracy of such a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that placental enlargement in fetal Hb Bart's disease can occur as early as in the late first trimester, and assessment of placental size is therefore clinically useful. For example, placental thickness assessed by 2D US at 11–14 weeks of gestation can differentiate fetuses with Hb Bart's disease from unaffected fetuses with a sensitivity of 70.0% and a specificity of 63.5% . However, a more reliable measurement technique of placenta size like 3D US and VOCAL, which is theoretically better than placental thickness, should improve the accuracy of such a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several disorders are associated with abnormal placental size, eg, small placenta caused by fetal growth restriction and aneuploidy or enlarged placenta in cases of hydrops fetalis caused by anemia. In our experience, placental thickness representing placental size, measured by two‐dimensional ultrasound (2D US), can be used as a sonomarker in predicting hemoglobin (Hb) Bart's disease among fetuses at risk . In the past, the measurement of placental thickness, rather than total volume, was used to estimate the placental size, whereas measurement of total placental volume, which is theoretically most accurate in estimation of placental size, is too complicated for routine use.…”
Section: Introductionmentioning
confidence: 99%
“…Hemodynamic changes caused by Hb Bart's disease can appear as early as 12-13 weeks of gestation [1][2][3] and myocardial workload secondary to anemia and hypervolemia may possibly occur in early gestation. Abnormal cardiac function may probably be an early subtle sign of fetal anemia occurring prior to development of hydrops fetalis.…”
mentioning
confidence: 98%
“…Theoretically, Tei index may be used to assess fetal ventricular myocardial performance in fetal anemia or hypervolemia due to various causes other than Hb Bart's disease or any condition associated with an increase in cardiac afterload. In most fetuses with Hb Bart's disease, anemia has occurred as early as in the first trimester leading to an increased cardiac output and hypervolemia to maintain tissue oxygenation and some degree of cardiomegaly can be visualized as early as 11-14 weeks of gestation [3,8]. Notably, ICT was the only one International Journal of Cardiology 184 (2015) 614-616 component of Tei index that was significantly increased, signifying that cardiac workload in the early phase of anemia is firstly involved in systolic dysfunction rather than diastolic function.…”
mentioning
confidence: 98%
“…Ultrasound signs of cardiac dysfunction can be detected during the early phase of fetal adaptation, such as cardiac enlargement before the presence of fetal hydrops. Cardiomegaly, which may be simply determined by cardiac diameter/thoracic diameter ratio (CTR), is a good sonographic marker for fetal anemia in early gestation [82][83][84] . In the late first and early second trimesters of pregnancy (12-15 weeks of gestation), a CTR cut-off value of 0.5 has a 90.7% sensitivity and a 97.2% specificity for Hb Bart's disease [83] .…”
Section: Fetal Cardiac Function In Early Pregnancymentioning
confidence: 99%